Cancer therapeutics-related cardiovascular dysfunction: Basic mechanisms and clinical manifestation. Issue 3 (March 2023) - Oikawa, Masayoshi; Ishida, Takafumi; Takeishi, Yasuchika
Abstract: Although recent advances in cancer treatment improve cancer prognosis, cancer therapeutics-related cardiovascular dysfunction (CTRCD) significantly contributes to the global burden of cardiovascular disease. CTRCD causes two crucial issues: first, premature treatment interruption or discontinuation of chemotherapy; second, the development of congestive heart failure during and after cancer treatment. Thus, early detection and prompt treatment of CTRCD may improve the prognosis in cancer patients. This review covers representative anticancer drugs, including anthracyclines, human epidermal growth factor 2 inhibitors, tyrosine kinase inhibitors, proteasome inhibitors, and immune checkpoint inhibitors. We focus on the molecular mechanisms of CTRCD and various approaches to diagnosis, prevention, monitoring, and treatment. Graphical abstract: Unlabelled Image Highlights: CTRCD significantly contributes to the global burden of cardiovascular disease. Comprehensive cardiac monitoring may be useful during and after cardiotoxic chemotherapy. Echocardiography and cardiac biomarkers play pivotal roles to detect CTRCD. Early detection and prompt treatment of CTRCD may improve the prognosis in cancer patients. Close collaboration between oncologists and cardiologists is becoming more and more important.